Psychometric Properties of Subjective Well-being Scale for Children (EBSNAM) - Mamani Flores, Leyla Noemi (2023)
To evaluate the psychometric properties of the scale of Subjective Well-being for Children(EBSNAM). Methodology: Quantitative and psychometric in scope, since it proposes the creationand validation of an instrument, being subjected to tests and statistical analyzes that will determine itsvalidity and reliability. Likewise, the research is characterized by being of a non-experimental design,since the variable was not manipulated and cross-sectional, because the information was collectedby applying the instrument in a determined time. Results: In the pilot study, favorable results wereobtained because 3 dimensions and 11 items were proposed for the creation of the Subjective Wellbeingfor Children scale (EBSNAM), taking into account the influential factors in the reliability andvalidity of the instrument. In the confirmatory study with a population of 1016 children, successfulresults were obtained in terms of reliability and validity (Cronbach’s Alpha 0.90) according to the mostappropriate model in 3 dimensions, which will allow us to validate and publish the Subjective Well-beingscale for Children. (EBSNAM). Conclusion: The Subjective Well-being for Children scale (EBSNAM)shows good internal consistency and construct validity.